8th European Conference on Rare Diseases & Orphan Products (ECRD 2016). Issue 1 (November 2016) - Schlander, Michael; Holm, Søren; Nord, Erik; Richardson, Jeff; Garattini, Silvio; Kolominsky-Rabas, Peter; Marshall, Deborah; Persson, Ulf; Postma, Maarten; Simoens, Steven; de Solà Morales, Oriol; Tolley, Keith; et al.
Table of contents O1 The European Social Preferences Measurement (ESPM) study project: social cost value analysis, budget impact, commercial life cycle revenue management, and the economics of biopharmaceutical Research & Development (R&D) Michael Schlander, Søren Holm, Erik Nord, Jeff Richardson, Silvio Garattini, Peter Kolominsky-Rabas, Deborah Marshall, Ulf Persson, Maarten Postma, Steven Simoens, Oriol de Solà Morales, Keith Tolley, Mondher Toumi, Harry Telser O2 Newborn Screening: the potential and the challenges James R Bonham O3 Untreatable disease outcomes - how would we measure them? Helmut Hintner, Anja Diem, Martin Laimer O4 Taking Integrated Care Forward: Experiences from Canada to inspire service provision for people living with rare disease in Europe Réjean Hébert O5 Listening to the patient's voice: social media listening for safety and benefits in rare diseases Nabarun Dasgupta, Carrie E. Pierce, Melissa Jordan O6 Via Opta:Mobile apps making visually impaired patients' lives easier Barbara Bori, Mohanad Fors, Emilie Prazakova O7 A report of the IRDiRC "Small Population Clinical Trial" Task Force Simon Day O8 HAE patient identification and diagnosis: An innovative, 'game changing' collaboration Thomas J. Croce Jr. O9 Co-creating with the community: primary packaging & administration for people with haemophilia Jonas Fransson, Philip Wood O10 Go with Gaucher, taking forward the next generation. How to involve young people to create a new generation of patient advocates Anne-Grethe Lauridsen, Joanne Higgs, Vesna Stojmirova Aleksovska P1 ODAK – Orphan Drug for Acanthamoeba Keratitis Christina Olsen, Ritchie Head, Antonio Asero, Vincenzo Papa, Christa van Kan, Loic Favennec, Silvana Venturella, Michela Salvador, Alan Krol P5 Rare Navigators help people living with rare diseases to manage the social – and healthcare systems Stephanie J. Nielsen, Birthe B. Holm P6 The eAcademy for Tay-Sachs & Sandhoff disease app Daniel Lewi, Patricia Durão P10 The role of a patient organisation in driving the research agenda in a rare disease Heather Band, Andrea West P13 Expertise for rare diseases mapped Marinda J.A. Hammann, Marije C. Effing-Boele, Hanka K. Dekker P14 The hidden costs of rare diseases: a feasibility study Amy Hunter, Amy Simpson P15 FDA's new natural history grant program: support to build a solid foundation for development of products for rare diseases Gumei Liu, Katherine Needleman, Debra Lewis, Gayatri Rao P17 Understanding the wider impact of adrenal insufficiency: patient organisation involvement in the TAIN project Amy Simpson, Amy Hunter, Martin J Whitaker P20 Bridging the gaps between medical and social care for people living with a rare disease Raquel Castro